Regulative measures in Malaysia towards illegal sale of medicine on facebook / Manzatul Azrul Azrie Sulaiman - Sulaiman, Manzatul Azrul Azrie (2017)
The sale of medicine in Malaysia had evolved according to time and advancement of technology. Medicines are now available through various channel from the traditional pharmacy and clinic setting to the revolutionary setup of online websites and Facebook platform. These changes and the rise of illegal online medicine had brought new challenges to the pharmacy enforcement officers enforcing the current laws. This research focus on the regulative measures currently available in Malaysia governing medicine sale on Facebook from the viewpoint of laws, enforcement activities and role of the relevant stakeholders. A qualitative approach was adopted with combination of both doctrinal and empirical research to gain maximum informations and ideas related to the field of research. The research finding shows that the current laws controlling the sale of medicines in Malaysia are obviously not equipped to deal with the arising problems brought upon by the internet and the expanding social media. Inadequacy of the laws to provide for specific provision on internet sale had left the enforcement agency warranting for control mechanism and enforcement power. These lacunas in the legislation requires urgent attentions and actions of the relevant stakeholders. The means to effectively control the situations lies squarely on the shoulder of the legislator, enforcement agency, pharmaceutical industry and consumer. Even with new laws in place, the problems will not cease to exist without active participation and commitment from all parties.